Peritoneal dialysis in acute renal failure - Gabriel, Daniela Ponce [UNESP]; Nascimento, Ginivaldo Victor R. [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP]; Martim, Luís Cuadrado [UNESP]; Barretti, Pasqual [UNESP]; Balbi, André Luis [UNESP] (Taylor & Francis, 2006)
The definition of adequate dialysis in acute renal failure (ARF) is complex and involves the time of referral to dialysis, dose, and dialytic method. Nephrologist experience with a specific procedure and the availability of different dialysis modalities play an important role in these choices. There is no consensus in literature on the best method or ideal dialysis dose in ARF. Peritoneal dialysis (PD) is used less and less in ARF patients, and is being replaced by continuous venovenous therapies. However, it should not be discarded as a worthless therapeutic option for ARF patients. PD offers several advantages over hemodialysis, such as its technical simplicity, excellent cardiovascular tolerance, absence of an extracorporeal circuit, lack of bleeding risk, and low risk of hydro-electrolyte imbalance. PD also has some limitations, though: it needs an intact peritoneal cavity, carries risks of peritoneal infection and protein losses, and has an overall lower effectiveness. Because daily solute clearance is lower with PD than with daily HD, there have been concerns that PD cannot control uremia in ARF patients. Controversies exist concerning its use in patients with severe hypercatabolism; in these cases, daily hemodialysis or continuous venovenous therapy have been preferred. There is little literature on PD in ARF patients, and what exists does not address fundamental parameters such as adequate quantification of dialysis and patient catabolism. Given these limitations, there is a pressing need to re-evaluate the adequacy of PD in ARF using accepted standards. Therefore, new studies should be undertaken to resolve these problems. Copyright © Informa Healthcare.
Keywords: Acute renal failure; Adequacy; Peritoneal dialysis; acute kidney failure; bleeding; electrolyte disturbance; extracorporeal circulation; hemodialysis; human; hyperglycemia; peritoneal dialysis; peritonitis; priority journal; protein depletion; review; uremia; Acute Kidney Injury; Humans; Kidney Failure, Acute; Peritoneal Dialysis; Treatment Outcome